PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA ORGANISASI MELALUI PEMBELAJARAN ORGANISASI DAN INOVASI PADA HOTEL PRAMA SANUR BEACH BALI - Justi Eaduwardo Makena (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2017)
The purpose of this research is to know the influence of transformational leadership, organizational learning and innovation on the performance of Prama Sanur Beach Bali organization. The research approach used is explanatory research type, with data collection method used by survey technique, using Likert scale in survey with interval of score between score 1-5, where score 1 shows very dissatisfied perception while score 5 shows perception very satisfied. The sample in this research is employees of Hotel Prama Sanur Beach Bali. In this study selected 81 people from a total of 420 employees of Hotel Prama Sanur Beach Bali. The analytical method used to determine the relationship between variables is the path analysis using the method PLS (Partial Least Square) with the help of software SmartPLS 2.0.Sebanyak four hypotheses of the eight proposed hypothesis accepted in this study. Some of the key findings of this research are: 1. Transformational leadership has an important impact on organizational performance, 2. Transformational leadership has an important impact on organizational learning, 3. Transformational leadership has no significant impact on innovation, 4. Organizational learning has no significant impact on innovation, 5. Organizational learning has an important impact on organizational performance, 6. Innovation has an important impact on organizational performance. Discussions about the results and research findings are discussed further with suggestions that can be addressed, among others, the importance of enriching the ability of leaders and knowledge models for organizational learning in order to give meaning to innovation in Hotel Prama Sanur Beach Bali.